IMPLEMENTATION OF A WEB-BASED SALES INFORMATION SYSTEM FOR COMPUTER NETWORKING EQUIPMENT AT MY RISE SIDOARJO - Hafid Pradana; Rohman Dijaya; Mochamad Alfan Rosid; Irwan Alnarus Kautsar (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: The rapid advancement of information technology has highlighted the need for efficient systems in sales data management. This study aims to develop and implement a web-based sales information system to enhance operational efficiency and customer service quality in My Rise, a store in Sidoarjo specializing in computer network equipment. Method: The research employed qualitative methods, including interviews to gather system requirements from business operators and direct observation to analyze the current sales process. The system was designed with an integrated approach to manage sales data, inventory, and transactions in real-time. Results: The implementation of the system resulted in significant improvements in the speed and accuracy of sales processes, with enhanced customer access to information and services. Novelty: This study introduces a practical web-based solution for small and medium-sized enterprises in the computer network equipment sector, addressing common issues such as data entry errors and delays in service, thus contributing to the digital transformation of the business.